From Trading Floors to Data Flows: How Financial Technologies Reshaped Market Efficiency and Risk - Umarova Shahzoda,; Shohruh Qutliboyev Sherzod o‘g‘li, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines the role of financial technologies in transforming the structure and functioning of modern financial markets. Rather than focusing on consumer-facing innovations, the study analyzes how digital trading systems, automated settlement mechanisms, and standardized financial data protocols altered market efficiency, liquidity, and risk dynamics. Using a qualitative analytical approach grounded in market microstructure theory and institutional economics, the paper explores how the transition from physical trading environments to electronic and algorithmic systems reduced transaction frictions while simultaneously introducing new forms of systemic risk. The findings suggest that financial technologies function as infrastructural forces that compress time, intensify information flows, and reshape the distribution of market power. The article contributes to the literature by framing financial technologies not merely as efficiency-enhancing tools, but as structural determinants of market behavior and stability.